Determination of Helicoverpa armigera (Lepidoptera: Noctuidae) larval instars and age based on head capsule width and larval weight - Stavridis, D. G.; Ipsilandis, C. G.; Katarachias, P. C.; Milonas, P. G.; Ifoulis, A. A.; Savopoulou-Soultani, M. (ENTOMOLOGIA HELLENICA, 2004)
Larνae of Helicoverpa armigera (Hubner) (Lepidoptera: Noctuidae) were reared in laboratory conditions (26°C, 16:8 L:D) and measurements of larval head capsule width, and body weight, were used in order to determine the boundaries of larval instars. Larvae of Η. armigera completed development in 5 to 7 instars. Head capsule width could predict the larval instar only for Ll. The upper boundary of head width for L1 was 0.4mm. Body weight could predict both L1 and L2 larval instars. Boundaries between L1-L2 instars were found to be 1 mg and for L2-L3 5,5 mg. Correlation and regression analysis suggest that a combination of head capsule width and body weight can predict both larval instars and chronological age under constant conditions in the laboratory.